2007
DOI: 10.1016/j.mce.2007.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation and proteasomal activity determine the transactivation properties of the mineralocorticoid receptor

Abstract: S0303-7207 (07) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.A c c e p t e d M a n u s c r i p t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 68 publications
4
27
0
Order By: Relevance
“…Interestingly we also showed that this aldosterone-induced MR phosphorylation is associated with a reduction in the MR protein level, as was previously described (53). Interestingly, Tirard et al (54) reported that a robust proteasome activity is required for optimal MR transactivation. Interestingly, finerenone likewise spironolactone totally blocked the aldosterone-induced MR phosphorylation, as well as its degradation, indicating that the antagonist compounds not only regulate receptor subcellular trafficking but also inhibit its turnover.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly we also showed that this aldosterone-induced MR phosphorylation is associated with a reduction in the MR protein level, as was previously described (53). Interestingly, Tirard et al (54) reported that a robust proteasome activity is required for optimal MR transactivation. Interestingly, finerenone likewise spironolactone totally blocked the aldosterone-induced MR phosphorylation, as well as its degradation, indicating that the antagonist compounds not only regulate receptor subcellular trafficking but also inhibit its turnover.…”
Section: Discussionsupporting
confidence: 88%
“…However, our finding is consistent with the observation that several nuclear receptors including GR are ubiquitinated and degraded in the course of their nuclear activities [21][22][23][24][25][26]. In addition to receptors, studies have revealed that coactivators, including steroid receptor coactivator 1 (SRC1), SRC2, SRC3, CBP and E6-associated protein (E6-AP), could also be ubiquitinated and degraded, through the proteosome, in order to disassemble and reassemble coactivator complexes, thereby promoting enhanced transcription [27].…”
Section: Bag-1m Is Not Involved In the Degradation Of Grsupporting
confidence: 92%
“…Mineralocorticoid receptors are SUMOylated at four acceptor sites clustered around AF-1. Their mutation allows mineralocorticoid receptors to synergistically activate a compound promoter but not the single palindromic PRE of the mouse mammary tumor virus promoter (38). GR are modified by SUMO-1 in vivo (39) and contain three consensus SUMO attachment sites, two in the N terminus at Lys-277 and Lys-293 in AF-1 and one in the LBD at Lys-703 (40).…”
Section: Human Progesterone Receptors (Pr)mentioning
confidence: 99%